2008
DOI: 10.1016/j.jcin.2008.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Survival Following Successful Percutaneous Coronary Intervention of Coronary Chronic Total Occlusions: Variability by Target Vessel

Abstract: The data suggest that PCI for CTO of the LAD, but not LCX or RCA, is associated with improved long-term survival. This information may assist in selecting patients for attempted CTO PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
3
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(85 citation statements)
references
References 25 publications
5
70
3
7
Order By: Relevance
“…240 According to this definition, Ն15% of patients undergoing PCI would be defined as having periprocedural MI. 241,242 Issues in procedure-related MI are discussed in Section 5.10.…”
Section: Pci Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…240 According to this definition, Ն15% of patients undergoing PCI would be defined as having periprocedural MI. 241,242 Issues in procedure-related MI are discussed in Section 5.10.…”
Section: Pci Complicationsmentioning
confidence: 99%
“…710 However, the impact of successful CTO recanalization on long-term survival remains unsettled. 701,711,712 The decision to try PCI for a CTO (versus continued medical therapy or surgical revascularization) requires an individualized risk-benefit analysis encompassing clinical, angiographic, and technical considerations. Consultation with a cardiothoracic surgeon and use of the Heart Team approach in cases of CTO in which a large territory is subtended and/or multivessel CAD is present are frequently done.…”
Section: Fondaparinux: Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…13,[33][34][35] However, the findings in the current literature regarding the potential relationship between CTO revascularization in patients with very low LVEF and improvement in mortality are inconsistent, as are the criteria for candidacy for ICD implantation. Otherwise, the possibility of LVEF improvement with its beneficial effect on survival provides the rationale for the technically demanding attempt to revascularize a CTO.…”
Section: Impact Of Cto On Mortalitymentioning
confidence: 99%
“…One could argue that the survival benefit after successful recanalization of a CTO might be limited to certain subgroups. This was demonstrated by Safley et al 19 who reported a significant benefit in survival after successful PCI of a CTO in the left anterior descending, but not in the left circumflex or RCA. In the context of ULM-PCI, revascularization of CTO-RCA is important to guarantee collateral circulation and provide reserve, if ULM restenosis were to occur.…”
Section: Discussionmentioning
confidence: 80%